Mrs. Claus takes a vacation - Alsenas, Linas (New York : Scholastic, 2006)
Tired of all the snow at the North Pole, Mrs. Claus takes a world tour before Christmas one year.
Keywords: Santa Claus -- Fiction; Travel -- Fiction; Christmas -- Fiction